Plant Diversity and Composition of Three Different Altitudes in Sikka Forest Area - East Nusa Tenggara - Fiqa, Abban Putri; Oktavia, Gebby Agnessya Esa (Biosaintifika: Journal of Biology & Biology Education, 2020)
East Nusa Tenggara located in the Wallacea area that has many endemic species. However, the existence of germplasm diversity in this area has been threatened due to landscape changes and deforestation. The research was conducted to identify floristic composition in Sikka forest area. This research also aimed to compare that plant composition in Sikka forest area on each of the different altitudes, including their diversity richness and environmental factors. Two sampling methods were used, which are Point-Centered Quarter (PCQ) method that applied for trees and nested sampling method 5x5 m2 for sapling and 2x2 m2 for ground cover. Measured parameters were Relative Density (RD), Relative Frequency (RF), Relative Coverage/dominance (RC), Important Value Index (IVI), Diversity Index (H'), and Jaccard Similarity Index (J’). Research results showed that the diversity index of each region was relatively low. Plant composition of tree, sapling, and groundcover in three different altitudes was quite different. This result indicates that the plant composition in the Sikka, East Nusa Tenggara is very diverse. The temperature and relative humidity in each altitude area observed was significantly different. One of the endemic species of Flores Island, Eucalyptus urophylla, was only found at 500-700 m asl. There are very limited research on the vegetation diversity held in Flores, East Nusa Tenggara. This research can be the basic for further research in order to explore the potential diversity of flora in this area.